First Grade intermediate Teachers' Evaluation of the Textbook Entitled (English for Iraq) (Journal of the College of Basic Education, 2022)
The current research aimed at evaluating the first grade intermediate textbook entitled English for Iraq (student's book) from the point of view of English teachers who are teaching it in General Directorate of Education in Baghdad Al-Rusafs/1 intermediate schools. The research's two questions were the following:1- What are the 1st grade intermediate teachers' viewpoints and evaluation of the English textbook entitled (English for Iraq) "student's book"? 2- Are there any significant differences at ( a=0.05) in the degree of the teachers' evaluation of the 1st grade intermediate English textbook entitled "English for Iraq"(student's book) according to the gender variable?. Sixty two first grade intermediate English teachers working in the intermediate schools of the General Directorate of Education in Baghdad- Al-Rusafa/1 during the academic year 2015-2016 was the sample of the research. Data were collected through a checklist. The responses were analyzed by using the proper statistics. The research findings indicated that the textbook in question is almost in harmony with the criteria mentioned in the used checklist, and can be used as an acceptable textbook to be taught to the students of the mentioned grade. This does not mean neglecting the diagnosed weaknesses identified by the present findings. It was also found that there were no significance differences in the degree of evaluation according to the gender variable. Finally, some recommendations and suggestions were presented by the researcher to support the evaluation process of other stages English textbook in Iraq.